2006
DOI: 10.1007/s00125-006-0259-7
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein B: a predictor of inflammatory status in postmenopausal overweight and obese women

Abstract: Aims/hypothesis: Inflammation is implicated in the development of type 2 diabetes and CHD, but the trigger of inflammation is unclear. Although in vitro and animal studies support a role of elevated levels of atherosclerotic lipoproteins in the activation of inflammation, plasma cholesterol cannot predict inflammatory markers in humans. Moreover, the association between inflammatory markers and other traditional risk factors of diabetes and CHD is unclear. To increase our knowledge of in vivo regulation of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 40 publications
(55 reference statements)
5
66
0
1
Order By: Relevance
“…In fact, CRP held in men a modest predictive ability independent of abdominal obesity only regarding dyslipidemia. Based on the finding that apo B was the primary predictor of inflammatory markers in nondiabetic postmenopausal women among a variety of risk parameters including adiposity and IR, 6 the expressed suggestion that high apo B would be associated with elevated risk of developing CHD and diabetes, may be extended further to developing hypertension, dyslipidemia and MS and to men. In the current study, the predictive ability by apo B of combined cardiometabolic disorders might be ascribed to the close relationship of apo B with subclinical inflammation.…”
Section: Sex Divergence In the Dynamics Of Cardiometabolic Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, CRP held in men a modest predictive ability independent of abdominal obesity only regarding dyslipidemia. Based on the finding that apo B was the primary predictor of inflammatory markers in nondiabetic postmenopausal women among a variety of risk parameters including adiposity and IR, 6 the expressed suggestion that high apo B would be associated with elevated risk of developing CHD and diabetes, may be extended further to developing hypertension, dyslipidemia and MS and to men. In the current study, the predictive ability by apo B of combined cardiometabolic disorders might be ascribed to the close relationship of apo B with subclinical inflammation.…”
Section: Sex Divergence In the Dynamics Of Cardiometabolic Riskmentioning
confidence: 99%
“…6 It was suggested that high apo B would be associated with elevated risk of developing coronary heart disease ((CHD) and) diabetes. Seeking differences among sexes in the association of apo B and other risk factors with the MS, Dallongeville et al 7 reported that the contribution of apo B to MS was significantly less in women than in men and suggested that different criteria are necessary to define the MS in women and men.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly plausible given our recent publication that showed that the number of apoB100-lipoproteins was the primary predictor of inflammatory markers in overweight and obese postmenopausal women, superior to all lipid levels and independent of adiposity. 28 Moreover, it is well accepted that larger LDL particles are less proinflammatory than smaller denser LDL particles. 43,44 Energy expenditure may be associated with leptin, 45,46 which is associated with inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…The postmenopausal women were included in the two studies if they (1) were overweight or obese with body mass index (BMI) X27 kg m À2 , 28 (2) aged between 46 and 70 years, (3) had biological confirmation of the menopause status (cessation of menstruation for more than 1 year and plasma follicle-stimulating hormone X30 U l À1 ), (4) were not taking hormone replacement therapy, (5) were non-smokers, and (6) were sedentary with o2 h per week of structured exercise. On physical examination and biological testing, all participants had no (1) diabetes (fasting glucose 47.1 mmol l À1 or 2-h plasma glucose of 411.1 mmol l À1 after a 75 g OGTT), (2) uncontrolled thyroid disease, cardiovascular or peripheral vascular disease, (3) use of hormone replacement therapy, estrogen, narcoleptics, steroids, lipid-lowering and antihypertensive agents, (4) dyslipidemia or hypertension requiring immediate medical intervention (total cholesterol 48 mmol l À1 , triglyceride 44.5 mmol l À1 , blood pressure 4160/100 mm Hg, (5) history of alcohol or drug abuse, (6) abnormal blood laboratory values (creatinine 4135 mmol l À1 ), (7) use of drugs or medications to stimulate weight loss, psychoactive drugs and adrenergic agonists by any route, (8) body weight fluctuation in the last 3 months (9) known history of inflammatory disease as well as cancer.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation